Youths and High School: Future perspectives - Zluhan, Mara Regina (2024)
Brazil has historically faced crises in high school education, and various reforms have aimed to overcome the challenges at this educational level. Currently, there is a new wave of policy reformulation in this area, as the current legislation presents weaknesses in its implementation. This qualitative research, of a bibliographic and documentary nature, intends to analyze youth culture and the significance of high school for young people so that they can recognize themselves in the curricula and daily school life. The high dropout and abandonment rates in high school should be a focal point for public policies, as education is the starting point for other professional, social, and cultural achievements. Considering the transformations in youth trajectories throughout history is fundamental for thinking about high school reforms, viewing education as a process of collective knowledge construction, and seeking the wholeness of the human being.